What Best Practices Improve Workplace Safety?. Issue 8 (1st August 2014) - Jacobs, Mike
Abstract : Workers are injured or killed at workplaces across North America every day. The best way to prevent such losses is to develop a solid, working accident prevention program. Systematically reviewing workplace operations, establishing correct job procedures, and ensuring all employees are properly trained can help prevent workplace injuries and illnesses.